New Jersey's postsuburban economy - Hughes, James W.; Seneca, Joseph J., 1943- (New Brunswick, N.J. : Rutgers University Press, 2015)
New Jersey has a long history of adapting to a changing economic climate. From its colonial origins to the present day, New Jersey''s economy has continuously and successfully confronted the challenges and uncertainties of technological and demographic change, placing the state at the forefront of each national and global economic era. Based on James W. Hughes and Joseph J. Seneca's nearly three-decade-long Rutgers Regional Report series, New Jersey's Postsuburban Economy presents the issues confronting the state and brings to the forefront ideas for meeting these challenges. From the rural agr.
Series Page; Title Page; Copyright Page; Contents; List of Figures; List of Tables; Preface; 1. Introduction and Overview; 2. The Structure of the New Jersey Economy and the Business Cycle; 3. The Broad Historical Evolution; 4. Transportation and the Economy; 5. The Wealth Belt; 6. Demography, the Economy, and Housing; 7. New Millennium, New Dynamics; Notes.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: New Jersey -- Economic conditions; New Jersey -- Conditions économiques.; Economic history; New Jersey